Pemanfaatan Limbah Bonggol Jagung Sebagai bahan Pembuatan Donat Untuk Peningkatan Perekonomian Di Desa Menjangan - Khasanah, Sufrotun; Yohandika Tri Apriliyanto (JURNAL INOVASI HASIL PENGABDIAN (JIHAN), 2024)
Menjangan Village has quite a lot of potential for corn crops, but the large amount of corn cob waste produced is mostly for animal feed. Corn cobs are a type of corn waste that can be used as processed food, one of which is corn cob flour. Corn cobs contain 23.3% lignin, 31.8% hemicellulose and 44.9% cellulose as well as high fiber content. The aim of this community service is that it is hoped that the people of Menjangan Village can utilize corn cobs which are currently only used as animal feed and are considered waste to become products that have high economic value and can keep the environment clean by reducing harvest waste. This community service was carried out using the socialization method regarding the use of corn cob waste as an ingredient for making donuts which was carried out in Menjangan village on January 19 2024. The results obtained from this socialization were an increase in community understanding about the use of corn cob waste so that it can be processed into products that have high economic value so that it can improve the economy of the Menjangan Village community. From the results of the socialization, the community gained an increased understanding of how to use corn cob waste as an ingredient for making donuts.